¿Sociología cuir en México? Apuntes sobre las tensiones conceptuales para los estudios sociológicos de la sexualidad - Torres Cruz, César; Moreno Esparza, Hortensia (El Colegio de México A.C., 2021)
Since the start of the twenty-first century, queer theory’s emergence in Latin America has triggered complex theoretical debates, particularly in the field of sociology where sexuality has been the subject of (limited) analysis since the 1970s. By reviewing some of the most important research into sexuality’s social aspects, this article seeks to analyze the conceptual precepts of sociological and cuir studies on sexuality in Mexico. The paper also proposes that a sociological-queer feminism can reveal—in a tense and situated interdisciplinary dialogue—various power mechanisms that shape sexuality in Mexico, as well as the complex possibilities of resignifying heteronormative mandates.